How Does AI Enable Early Detection of Developmental Disorders? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2016)
Developmental disorders, a group of conditions with physical, learning, language, or behavioral impairments, present a significant challenge to healthcare sy...
Keywords: AI in Pediatrics; Enable; Early; Detection; Artificial Intelligence; Machine Learning; Healthcare